Management of febrile neutropenia in the perspective of antimicrobial de-escalation and discontinuation. Issue 12 (2nd December 2019) - Schmidt-Hieber, Martin; Teschner, Daniel; Maschmeyer, Georg; Schalk, Enrico
ABSTRACT: Introduction : Infections are among the most frequent complications in patients with hematological and oncological diseases. They might be classified as fever of unknown origin and microbiologically or clinically documented infections. Optimal duration of antimicrobial treatment is still unclear in these patients. Areas covered : We provide an overview on the management of febrile neutropenia in the perspective of antimicrobial de-escalation and discontinuation. Expert opinion : Patients with febrile high-risk neutropenia should be treated empirically with an anti-pseudomonal agent such as piperacillin/tazobactam. Several clinical studies support the assumption that the primary antibiotic regimen might be safely discontinued prior to neutrophil reconstitution if the patient is afebrile for several days and all infection-related symptoms have been resolved. Primary empirical treatment with carbapenems or antibiotic combinations should commonly only be considered in selected patient subgroups, such as patients with severe neutropenic sepsis or colonization with multidrug-resistant bacteria. Preemptive antifungal treatment guided by lung imaging and other parameters (e.g. serial Aspergillus galactomannan antigen screening) might reduce the consumption of antifungals compared to the classical empirical approach. Multidrug-resistant pathogens are emerging, and novel anti-infective agents under development are scarce. Therefore, a rational use of antimicrobials based on the principles of antibiotic stewardship is crucial.